Change‐point analysis through integer‐valued autoregressive process with application to some COVID‐19 data. (11th July 2021) - Chattopadhyay, Subhankar; Maiti, Raju; Das, Samarjit; Biswas, Atanu
Abstract: In this article, we consider the problem of change‐point analysis for the count time series data through an integer‐valued autoregressive process of order 1 (INAR(1)) with time‐varying covariates. These types of features we observe in many real‐life scenarios especially in the COVID‐19 data sets, where the number of active cases over time starts falling and then again increases. In order to capture those features, we use Poisson INAR(1) process with a time‐varying smoothing covariate. By using such model, we can model both the components in the active cases at time‐point t namely, (i) number of nonrecovery cases from the previous time‐point and (ii) number of new cases at time‐point t . We study some theoretical properties of the proposed model along with forecasting. Some simulation studies are performed to study the effectiveness of the proposed method. Finally, we analyze two COVID‐19 data sets and compare our proposed model with another PINAR(1) process which has time‐varying covariate but no change‐point, to demonstrate the overall performance of our proposed model.